2016
DOI: 10.1002/cm.21339
|View full text |Cite
|
Sign up to set email alerts
|

Cargo rigidity affects the sensitivity of dynein ensembles to individual motor pausing

Abstract: Cytoplasmic dynein is a minus-end directed microtubule-based motor protein that drives intracellular cargo transport in eukaryotic cells. Although many intracellular cargos are propelled by small groups of dynein motors, the biophysical mechanisms governing ensemble motility remain largely unknown. To investigate the emergent motility of motor ensembles, we have designed a programmable DNA origami synthetic cargo "chassis" enabling us to control the number of dynein motors in the ensemble and vary the rigidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
(98 reference statements)
0
15
0
Order By: Relevance
“…The mechanical interaction between two coupled motors also depends on the stiffness of the cargo and properties of the motor (15,27,28). Here we showed that two myoVc motors have longer run lengths when coupled via a flexible DNA linker compared with a rigid linker.…”
Section: Myovc Molecules Coordinate To Transport Cargomentioning
confidence: 76%
“…The mechanical interaction between two coupled motors also depends on the stiffness of the cargo and properties of the motor (15,27,28). Here we showed that two myoVc motors have longer run lengths when coupled via a flexible DNA linker compared with a rigid linker.…”
Section: Myovc Molecules Coordinate To Transport Cargomentioning
confidence: 76%
“…Our data raise the possibility these faster speeds are due to more two-dynein complexes. However, previous reports suggested that whereas artificially tethering dyneins increased run length, it had little or no effect on velocity 26 , 27 .…”
Section: Two Dyneins Increase Force and Speedmentioning
confidence: 79%
“…Our data raise the possibility these faster speeds are due to more complexes containing two dyneins. However, artificial tethering of processive dynein or kinesin motors had suggested motor number has little or no effect on velocity (Derr et al 2012;Jamison et al 2012;Furuta et al 2013;Driller-Colangelo et al 2016).…”
Section: Two Dyneins Increase Force and Speedmentioning
confidence: 99%